Immobilization mechanism of Gd2Zr2O7 ceramic for nuclear waste treatment. Issue 24 (15th December 2022) - Wei, Guilin; Shu, Xiaoyan; Wen, Mingfen; Lu, Yuexiang; Duan, Tao; Chen, Shunzhang; Tang, Hexi; Chen, Jing; Dong, Faqin; Xie, Yi; He, Yang; Lu, Xirui
Abstract: Nuclear waste generated from the nuclear industry should be safely treated because of its harmful effects on the environment and humans. In this study, the mechanism of the as-prepared Gd2 Zr2 O7 for nuclear waste immobilization was investigated as an example in the simulation of waste immobilization under spark plasma sintering (SPS) conditions. The solid solubility limit of the waste in the sintered matrices was 45 mol% at 1725 °C and 1800 °C. The phase transformation from fluorite to pyrochlore could be detected owing to the increase in the ionic radius ratio when the waste was immobilized in the matrix structure. A high sintering temperature promotes transformation by increasing the orderliness of the matrix structure and destroying the crystalline structures to form an amorphous structure, results in a decrease in structural orderliness. Moreover, the leaching rates of Nd, at approximately 3.5 × 10 −8 g·m −2 ·d −1 at 42 d, demonstrated high chemical stability in the matrices doping with 45 mol% simulated nuclear waste. A mechanism is proposed in this study for treating radioactive waste using Gd2 Zr2 O7 ceramic under SPS conditions. Graphical abstract: Image 1